IJTIHAD OF THE JUDGE IN DETERMINING THE HADHANAH OF A CHILD WHO HAS NOT BEEN MUMAYIZ TO THE BIOLOGICAL FATHER - Albab, Muhamad Ulil (Faculty of Law Universitas 17 Augustus 1945 Cirebon, 2024)
This study examines the juridical reasons behind a judge’s decision to grant child custody (hadhanah) to the biological father, despite the child not reaching the age of maturity, deviating from Article 105 letter (a) of the Compilation of Islamic Law. Using normative legal research methods, the study analyzes laws, court rulings, and legal concepts. The findings show that the judge’s primary considerations were the best interest of the child and maslahah mursalah, factoring in parental conflicts, mediation agreements, and the child’s stable environment. This ruling can be justified philosophically based on maqashid al-shari’ah and aligns with the Child Protection Law. However, it raises issues of gender equality and the child’s need for a maternal attachment figure. The decision reflects a shift in Indonesian Islamic family law toward stronger child protection, but it requires strengthening post-verdict supervision mechanisms to ensure its effective implementation and address potential complexities in child custody cases